Cytotoxic effect of three species of Centaurea genus on acute lymphoblastic leukemia cell line (Nalm-6) - Ahmad Gharehbaghian; Forouzan Bahmani; Somayeh Esmaeili; Davood Bashash (Institue of Medicinal Plants, ACECR, 2018)
Background: Medicinal plants are considered as one of the ideal therapeutic sources for cancer prevention or treatment due to their bioactive contents and low side effects to humans. Centaurea genus have shown potential anti-tumor activity on some cancer cell lines in previous studies. Objective: The aim of this study was to evaluate the cytotoxic effect of three species of Centaurea genus (C. albonitens, C. pseudoscabiosa, C. salicifolia) on Nalm-6 cells. Methods: Nalm-6 cells were treated with increasing concentrations of the methanolic extracts of the aerial parts of three Centaurea species, then, their cytotoxic and anti-proliferative effects were evaluated using trypan blue, MTT and DAPI staining assays. Moreover, annexin V/PI staining and cell cycle analysis were performed for further investigation. Results: The results of trypan blue, MTT assay and DAPI staining revealed that all 3 extracts exhibit cytotoxic and anti-proliferative properties against Nalm-6 cells in a dose- and time-dependent manner (p≤0.001). Interestingly, there was no considerable cytotoxicity in normal cells, MDBK. The flow cytometric analysis validated that Centaurea dose dependently induces apoptosis and G1 phase arrest in Nalm-6 cells (p≤0.01). Conclusion: Due to the safety profile of the natural products, our study suggests that Centaurea extracts might provide insight into a novel therapeutic strategy and may confer advantages for acute lymphoblastic leukemia treatment, however further researches are necessary.